Environmental Law and Economic Law Review: Is Green Economy and Environmental, Social, and Governance (ESG) Green Economy or Greenwashing? - Latif, Birkah; Shah, Mohammad Qadam; Daud, Aidir Amin; Napang, Marthen; Liman, Padma D.; Camelia, Indah; Syarif, La Ode M.; Rifai, Andi Tenri Famauri; Ali, Aldi Yusa; Gloria, Adelin Yohana (Indonesian Journal of International Law, 2024)
In implementing the SDGs according to the principle of green economy, countries are competing to apply the ESG concept which aims to identify all non-financial risks and opportunities related to the company's routine, especially those related to Environment (E), Social (S), and Governance (G), to achieve sustainability development in business through corporate actions. Such well-founded implementation within a company will generate a positive impact and increase the appeal for investors amid today's fierce business competition. The ESG is expected to be the key in promoting economic improvement without sacrificing environmental aspects.